Etude et optimisation des parametres du procede pour le controle du retour elastique de pieces embouties - Ghouati, Omar; Joannic, David; Gelin, Jean-Claude (European Journal of Computational Mechanics, 1998)
A numerical technique for the control of springback effects is proposed in this paper. This technique is based on the combination of an optimisat ion algorithm and a finit e element method. The optimization algorithm is based on a gradient method containing a sensitivity analysis and allows the optimization of the process parameters in order to obtain a final product with the desired shape. Numetical examples are presented to illustrate the efficiency of the proposed approach.